Analysis of Bread Production Facilities Layout using BLOCPLAN Algorithm - Imanullah, Harry; Heryani, Hesty; Nugroho, Agung (Department of Agro-industrial Technology, University of Brawijaya, 2021)
AbstractThis study aims to obtain an optimal facility layout by considering the distance between the workstations, transfer time, and material handling cost in a bakery. The research was conducted at a medium-scale bread producer CV Mumtaz Bakery in Banjarbaru City, South Kalimantan. The initial layout of CV Mumtaz Bakery's production facilities is considered as not optimal for production capacity up to 500 kg per day. The layout analysis and the appearance of improvement alternatives were carried out using the BLOCPLAN algorithm, and then the design implementation was carried out using CorelDraw software. Determination of the best layout alternative is based on the highest R-Score. The results showed that the best layout was the one with an R-Score of 0.86. This selected workstation layout has a total distance between processing stations of 31.70 m, a total transfer time of 25 seconds, and a material handling cost of IDR 434.29 for each batch. This layout will reduce the total material transfer distance and the material transfer time from the initial layout by 14.67% and 10.7% respectively.Keywords: BLOCPLAN, bread production, facilities layout, material handling cost AbstrakPenelitian ini bertujuan untuk memperoleh alternatif tata letak fasilitas yang lebih optimal dengan mempertimbangkan jarak antar proses produksi, waktu perpindahan, serta biaya penanganan bahan pada sebuah bakery. Penelitian dilakukan di CV Mumtaz Bakery yang merupakan produsen roti skala menengah di Kota Banjarbaru, Kalimantan Selatan. Tata letak fasilitas produksi CV Mumtaz Bakery dinilai masih belum optimal untuk kapasitas produksi hingga 500 kg per hari. Analisis tata letak dan penentuan alternatif perbaikan dilakukan menggunakan algoritma BLOCPLAN kemudian implementasi desain dilakukan dengan software CorelDraw. Penentuan alternatif tata letak terbaik berdasarkan pada R-Score tertinggi. Hasil penelitian menunjukkan bahwa tata letak terbaik adalah alternatif dengan R-Score sebesar 0,86. Tata letak fasilitas yang terpilih tersebut mempunyai total jarak antar fasilitas produksi sebesar 31,70 m, total waktu perpindahan 25 detik, dan biaya penanganan bahan Rp434,29 untuk setiap batch. Penerapan tata letak ini akan menurunkan total jarak perpindahan material dan waktu perpindahan bahan dari tata letak awal secara berturut-turut sebesar 14,67% dan 10,7%.Kata kunci: BLOCPLAN, biaya penanganan bahan, produksi roti, tata letak fasilitas